2015
DOI: 10.17957/tpmj/15.3027
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Endoscopic Biopsy; Morphological Spectrum of Lesions

Abstract: … Background: Upper GI endoscopy is an established procedure for investigating a wide range of upper GI conditions especially inflammatory and malignant diseases of stomach and esophagus. A good correlation in diagnosis can be achieved by complementing endoscopic findings with histology of biopsy specimens. Aims and objectives: 1) To evaluate morphological patterns of upper GI conditions. 2) To correlate endoscopic characterization of upper GI lesions with histopathological assessment of biopsy specimens. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 1 publication
(1 reference statement)
4
21
1
Order By: Relevance
“…In proved cases, any sign of dysplasia especially high grade dysplasia, advocates colectomy as the next immediate intervention. [10] Gastritis can be classified into chronic superficial, chronic nonspecific, erosive gastritis, gastritis with intestinal metaplasia and H. pylori positive gastritis. We came across 02 (1.01%) cases of chronic nonspecific gastritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In proved cases, any sign of dysplasia especially high grade dysplasia, advocates colectomy as the next immediate intervention. [10] Gastritis can be classified into chronic superficial, chronic nonspecific, erosive gastritis, gastritis with intestinal metaplasia and H. pylori positive gastritis. We came across 02 (1.01%) cases of chronic nonspecific gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…[10] We had only 02 cases of acute and acute on chronic inflammation of the duodenum. Neil A Shepherd et al, showed considerable non-neoplastic lesions affecting the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the incidence of dysplasia of the oesophagus was 0.8% and it was 4.1% in Memon F, et al's study group 13 . Dysplasia of the oesophagus either progress from low grade to high grade or regress.Waf1p21 reactivity decreases in the dysplastic epithelium whereas immuno reactivity for PCNA and P53 increase 14 . In our study 65.57% of the cases had squamous cell carcinoma which was in consistent with Memon F, et al's study [78.6%] 13 …”
Section: Resultsmentioning
confidence: 91%
“…This operator opted for the selection of all strong individuals corresponding on the basis of fitness values (Memon et al, 2015). All population have a certain value of fitness level.…”
Section: Selectionmentioning
confidence: 99%
“…The majority has been done using optimization for the sake of minimum energy consumption (Memon et al, 2015). Hence, the optimization is an efficient method for optimizing both the route and energy of the sensor node and WSNs.…”
Section: Introductionmentioning
confidence: 99%